STREET DANCE: A BRANCH OF SPORTS FOR ALL - Petracovschi S. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2012)
The aim of this paper is to analyze the Street dance as a phenomenon, together with other sportive activities such as street ball, roller, BMX or skateboarding, is now being practiced also by Romanian teenagers. Its main trait is the lack of institutionalisation when organised, wholly depending on the free will of those practicing it, but which gains a sportive character through the training process and the competitions organised between teams. The purpose of this research is to analyse the influence of sports on the street dance phenomenon, seen as a subculture of sports and the way in which dancers identify themselves with the sport with the aim of integrating it as a branch of sports for all. Observation and the survey questionnaire were the research methods used. A demographic questionnaire was developed and the Athletic Identity Measurement Scale was applied to 150 dancers (male and female) from Timisoara. The results indicate the fact that the dancers identify themselves with athletes to a significant extent.